Pircinque: new strawberry cultivar for Brazilian producers Pircinque: nova cultivar de morangueiro para os produtores brasileiros - Fagherazzi A.F.* (2021)
© 2021, Sociedade de Olericultura do Brasil. All rights reserved.The strawberry cultivar ‘Pircinque’ was developed by the breeding program of Consiglio per la Ricerca in Agricoltura e l’Analisi dell’Economia Agraria-Centro di Olivicoltura, Frutticoltura e Agrumicoltura (CREA-OFA-FRF), an Italian research entity, and introduced in Brazil in 2013 by the Centro de Ciências Agroveterinárias da Universidade do Estado de Santa Catarina (CAV-UDESC). In the breeding program in which it originated, ‘Pircinque’ was selected for plant rusticity and resistance to soil pathogens. It can be cultivated where soil sterilization techniques are not used. In Brazil, the cultivation of ‘Pircinque’ has shown to be promising in the major strawberry producing regions. The main characteristics that allowed the development of this cultivar among the growers were plant vigor, productivity, rusticity, flavor, pulp firmness, crispness, sweetness and fruit color. When grown with excessive nitrogen fertilization fruit sensitivity to Botrytis cinerea fungal attack has been found, and a high vegetative plant growth. Due to fruits peculiarity, many growers make differentiated sales, adding value to quality product. Also, due to the high post-harvest period, many growers allocate part of the production to more distant locations. These characteristics are determinant for the cultivar Pircinque be distinguishable from other strawberry cultivars already marketed in Brazil. The cultivar was registered at the Ministério da Agricultura, Pecuária e Abastecimento (MAPA) in 2016, and the commercialization of plants started in 2017 with five nurseries accredited to produce and market ‘Pircinque’ plants throughout Brazil.